Yeast biodiversity in the vineyards of the Azores Archipelago (Portugal) - Neves, J. Drumonde (2012)
This study aims to identify the fermentative yeasts communities of the vineyards from the mid-Atlantic islands ecosystems of the Azores Archipelago and to evaluate whether the populations vary according to the islands geography, grape variety and type of vineyard. From an ecological point of view, vineyards of these isolated volcanic islands terroirs correspond to very particular ecosystems, whose yeast flora is completely unknown. During the harvests of 2009 and 2010, 88 and 75 grape samples were collected from eight islands of the archipelago, respectively. They were obtained from traditional grape varieties (Arinto, Verdelho and Terrantez) and hybrid varieties. The sampling plan covered 36 locations, including vineyards in appellations of origin and vineyards that were abandoned for at least 5 years. A total of 4890 yeast isolates was obtained from the crushed grapes. Species identification was performed by restriction fragment length polymorphism analysis (RFLP) and sequencing of ITS regions. Twenty-seven yeast species were identified, being Hanseniaspora uvarum, Issatchenkia terricola, Candida zemplinina and Metschnikowia pulcherrima the most representative ones. Three putative new species were also found. In 2009, differences in the microflora composition were apparent between islands, grape varieties and type of vineyard. A high percentage of C. zemplinina differentiated the yeast microflora of the eastern islands Santa Maria and São Miguel (25% and 36%, respectively). The species M. pulcherrima appeared associated with the traditional grape varieties (20% and 2% in traditional and hybrid varieties, respectively). H. uvarum was found in higher proportions in abandoned vineyards (53% and 43% in abandoned and non-abandoned vineyards, respectively). In the following sampling year, characterized by unfavorable climatic conditions and very low grape production, the yeast species richness decreased considerably from 25 species in 2009 to 14 species in 2010 and H. uvarum represented 86% of the total isolates, 40% more than in the previous year.